PTH-047 Differences in luminal distribution and clinical characteristics of crohn's disease in south asians and white british in the north of england. (22nd June 2015) - Khan, MA; Newman, W; Hill, WJ
Abstract : Introduction: Inflammatory bowel diseases (IBD) are inflammatory conditions that affect the gastrointestinal tract and may have extra intestinal manifestations. The two main subtypes are Crohn's disease (CD) and ulcerative colitis (UC). The incidence of IBD has traditionally been higher in Caucasian populations in Europe, North America and Australia compared to other regions of the world. There is now evidence of increasing incidence in all populations worldwide. Studies from the UK, North America, Malaysia and Singapore have observed a 2–3 times higher incidence of IBD in South Asian immigrant populations compared to local cohorts. However, few studies have described the diseas phenotype and mucosal distribution in the South Asian immigrant population. Method: Ethics approval was obtained ref: O5/Q1407/274. Patients were recruited prospectively in 11 centres in the North Of England. Inclusion criteria were diagnosis of CD and age >16 years. Exclusion criteria were Diagnosis of IBDU or IDC and Age <16 years. Information was collected from using a standard clinical proforma. Data was stored on and analysed on a FileMaker Pro database. Chi Squared analysis was used to compare groups. Results: In total, 128 South Asians (SA) and 426 White British. In the South Asian cohort more males than females were affected compared to White British cohort, which had the opposite trend. South Asians were most likely to be diagnosed with Colonic disease (L2) compared to White British (50% vs. 24% respectively), which was highly statistically significant (p = 1 × 10 –6 ). Differences in each luminal distribution group (L1–L4) were statistically significant in both groups. In addition differences in disease behaviour were statistically significant for B1 and B2 disease but was not significant for B3 disease. South Asians were less likely to be diagnosed over the age of 40 (A3) compared to White British which was statistically significant (p = 0.02). There was no statistical difference in positive family history or EIM's between groups. South Asians were less likely to need surgery compared to Caucasians (29% vs. 58%), which was highly significant. Conclusion: There are significant differences in luminal distribution, age of diagnosis and need for surgery between groups. South Asians are less likely to need surgery suggests a less severe phenotype compared to White British. These differences may represent differences in disease pathogenesis in particular genetic susceptibility or environmental factors. This information will help inform current and future genotype studies. Disclosure of interest: None Declared.